Crime should not pay. Iceland and the International Developments of Criminal Assets Recovery - Arnar Jensson 1955- (2011)
This study concludes that present circumstances related to the collapse of the three largest Icelandic banks in fall of 2008 and the fact that around 90 criminal investigations are ongoing against many of their directors, managers and largest shareholders call for extraordinary measures to be implemented. The most powerful legal instrument to retrieve the vast sums allegedly transferred out of these banks before their collapse is non-conviction based confiscation under civil legal procedures. This modern instrument is the centrepiece of a new, progressive assets recovery model for Iceland, recommended in the final chapter of this paper. Globalization has not only abolished barriers of communication, opened up global markets and interconnected gateways but also birthed new criminal opportunities. With ever increasing profits, serious international crime has made it possible for the leaders to distance themselves from the actual criminal acts, rendering a conviction nearly unattainable. In recent years most state authorities and international organizations have realized that traditional approach of pursuing criminal sanctions against serious, international crime has failed because of the immense proceeds it generates. The new international approach has been called “proceeds of crime strategy” or “assets recovery strategy”, where illegal revenues and assets of the alleged offenders are directly targeted. Iceland has been slow to react on these international developments. Comparison between measures taken in Iceland and EU, Ireland and Norway reveals that Iceland is far behind these countries. Firstly, Iceland has neither governmental nor law enforcement policy in this area, resulting in de-motivating effects through the administration and the law enforcement. Secondly, Icelandic authorities need to strengthen the legal framework considerably, both domestic legal provisions and cooperation agreements on mutual assistance and orders for seizures, freezing and confiscation of criminal assets. Thirdly, Iceland does not ...